Islam dan Tata Masyarakat Dunia - Masri Mansoer (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
The structure of world life is colored by various ideologies. Each ideology offers a perfect future. Socialism glorifies collectivism and disregards individuality, aiming ultimately to fulfill material needs collectively. Conversely, capitalism (liberalism) places humans as free individuals with the right to determine their own lives and do whatever is deemed good and right to achieve profit for themselves. From these two major ideologies in the world, Islam does not deny or position itself on either pole. Islam places itself in synthesis and becomes an alternative among the various extremist tendencies of ideologies in a balanced and fair manner. Therefore, the relationship Islam seeks to build is one of partnership and cooperation that mutually benefits the well-being of all human beings. This paper discusses the universal aspect of Islam as a perfect foundation for constructing a global societal order.